Discrimination of different storage time of the pork by electronic nose - HONG Xue-zhen; WANG Jun; ZHOU Bo; WANG Yong-wei (浙江大学学报. 农业与生命科学版)
An electronic nose (e-nose, PEN 2) was employed to classify the pork groups with different storage times (0-6 d). To acquire the optimum experimental procedure, the method of analysis of variance (ANOVA) was adopted. The results showed that the mass of the pork samples affected highly significantly the result of discrimination, and next was the headspace-generated time. By applying one-way ANOVA and discrimination power (DP), the optimum experimental parameters were acquired: 10 g sample with 5 min headspace-generated time. The later experiment was taken under the optimum experimental parameters, and the principle components analysis (PCA), as well as linear discriminant analysis (LDA) were employed. The result showed that e-nose with the optimum parameters could classify the samples stored 0-6 d well.